Association of Matrix Metalloproteinase 8 Genetic Polymorphisms with Bronchial Asthma in a Japanese Population - Terufumi Shimoda M.D., Ph.D.; Yasushi Obase M.D., Ph.D.; Reiko Kishikawa M.D., Ph.D.; Tomoaki Iwanaga M.D., Ph.D. (Allergy & Rhinology, 2013)
Asthma has a strong genetic component. The final disease phenotype results from complex interactions between environment and multiple genes of small-to-modest effects. We investigated whether the polymorphism in genes encoding inflammatory mediators and cytokines is important for solving the onset and progression of asthma. We investigated whether 31 single nucleotide polymorphisms (SNPs) in genes encoding cytokines or monokines (interleukin [IL]-5R, matrix metalloproteinase [MMP] 8, beta2 adrenergic receptor, cytotoxic T-lymphocyte-associated antigen 4, IL-3, C-reactive protein, cytochrome P450 (CYP) 2C9, CYP3A4, a disintegrin and metalloproteinase [ADAM] 33, cysteinyl leukotriene receptor [CysLTR] 1, CysLTR2, eosinophilic cationic protein, glucocorticoid receptor, and leukotriene A 4 hydrolase) are related to asthma development in 206 Japanese bronchial asthma patients and 127 healthy controls. Using multifactor dimensionality reduction (MDR), we identified rs17099451 in MMP8, using a single locus model, with a mean cross-validation of 87.0%. Using a two-locus model, combinations of MMP8 and rs44707 in ADAM33, and MMP8 and rs40401 in IL-3, were identified, with mean cross-validation consistencies reaching 45.0%. Of the SNPs selected by the MDR method, rs17099451 in MMP8 and rs40401 in IL-3 were regarded as the most significant results in a 2 × 2 dominant model analysis. The finding that an MMP8 allele was most strongly related to asthma development indicates that metalloproteinase function is crucial to the airflow limitation process involved in this disease.